MicroRNA-141 enhances anoikis resistance in metastatic progression of ovarian cancer through targeting KLF12/Sp1/survivin axis. Issue 1 (December 2017) - Mak, Celia; Yung, Mingo; Hui, Lynn; Leung, Leanne; Liang, Rui; Chen, Kangmei; Liu, Stephanie; Qin, Yiming; Leung, Thomas; Lee, Kai-Fai; Chan, Karen; Ngan, Hextan; et al.
Abstract Background Cancer metastasis is determined by the formation of the metastatic niche and the ability of cancer cells to adapt to microenvironmental stresses. Anoikis resistance is a fundamental feature of metastatic cancer cell survival during metastatic cancer progression. However, the mechanisms underlying anoikis resistance in ovarian cancer are still unclear. Methods Expressions of miRNA-141 and its downstream targets were evaluated by qPCR, Western blotting, Immunohistochemical (IHC) andin situ hybridization (ISH) assays. The luciferase assays were used to prove KLF12 as the downstream target of miR-141. The cDNA microarray and apoptotic protein arrays were used to identify the targets of miR-141 and KLF12. The competition of KLF12 and Sp1 on survivin promoter was examined by ChIP assay. IHC analysis on ovarian cancer tissue array was used to evaluate the expressions of KLF12 and miR-141 and to show the clinical relevance. The functional studies were performed by in vitro and in vivo tumorigenic assays. Results Enforced expression of miR-141 promotes, while knockdown of miR-141 expression inhibits, cell proliferation, anchorage-independent capacity, anoikis resistance, tumor growth and peritoneal metastases of ovarian cancer cells. Bioinformatics and functional analysis identified that Kruppel-related zinc finger protein AP-2rep (KLF12) is directly targeted by miR-141. Consistent with this finding, knockdown of KLF12 phenocopied the effects of miR-141 overexpression in ovarian cancer cells. In contrast, restoration of KLF12 in miR-141-expressing cells significantly attenuated anoikis resistance in ovarian cancer cells via interfering with Sp1-mediated survivin transcription, which inhibits the intrinsic apoptotic pathway and is crucial for ovarian cancer cell survival, anoikis resistance and peritoneal metastases. Immunohistochemical (IHC) and in situ hybridization (ISH) assays confirmed that miRNA-141 expression is inversely correlated with KLF12 expression and significantly associated with advanced ovarian cancers accompanied with distal metastases, underscoring the clinical relevance of our findings. Conclusions Our data identify a novel signaling axis of miR-141/KLF12/Sp1/survivin in enhancing anoikis resistance and likely serves as a potential therapeutic target for metastatic ovarian cancer.